Mechanical transmission of enterotoxigenic Escherichia coli to weaned pigs by people, and biosecurity procedures that prevented such transmission - Amass, SF; Halbur, PG; Byrne, BA (Journal of Swine Health and Production, 2003)
Objectives: To determine whether people can mechanically transmit enterotoxigenic Escherichia coli (ETEC) from infected to susceptible weaned pigs during direct pig contact and to determine biosecurity measures that will prevent such transmission.Materials and methods: One hundred and twenty-five 19- to 21-day-old weaned pigs, culture-negative for ETEC M1823B, were randomly allocated to six treatment groups housed in five separate isolation rooms. Inoculated Pigs were offered 1.36 x 1010 to 8.92 x 1010 colony forming units of E coli mixed in strawberry gelatin on two occasions. Pen Sentinels were housed with Inoculated Pigs. A caretaker fed pigs, checked waterers, and directlycontacted each group of pigs for 10 minutes daily for 10 consecutive days. The caretaker contacted Inoculated Pigs and moved directly to Direct Sentinels, recontacted Inoculated Pigs, washed hands twice, changed outerwear, then contacted Hand-wash Sentinels. The caretaker then recontacted Inoculated Pigs, showered, changed outerwear, and contacted Shower Sentinels. Non-exposed pigs had a separate caretaker.Results: Escherichia coli M1823B was isolated from all 20 Inoculated Pigs, all five Pen Sentinels, 20 of 25 Direct Sentinels, and 23 of 25 Hand-wash Sentinels. The 25 Shower Sentinels and 25 Non-exposed Pigs remained culture-negative for M1823B.Implications: In this study, people mechanically transmitted E coli without extraordinary measures to enhance caretaker contact with pig excretions and secretions beyond that which would occur in a typical pork production unit. Hand washing and donning clean outerwear did not prevent E coli transmission. However, showering and donning clean outerwear did prevent transmission.
Keywords: swine; post-weaning diarrhea; Escherichia coli; transmission; biosecurity